قضية الاشتقاق في مجال فقه اللغة العربية: مفهومه وأنواعه والأصل فيه / DERIVATION IN ARABIC FIQH: CONCEPTS, TYPES AND ORIGINS - Djuaeni, Muhammad Napis; Hamzah, Hamzah (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2021)
تشتهر اللغة العربية بمفرداتها الشائعة. والاشتقاق هو من إحدى طرق تكوين المفردات العربية. وهو لا يزال عند علماء اللغة العرب القدماء أو المتحدثين يتجادلون حول تصنيفه وما هو أصل الاشتقاق هل هو المصدر أو الفعل. فيهدف هذا البحث إلى معرفة حقيقة الاشتقاق في مجال فقه اللغة العربية سواء كان مفهومه وتصنيفه وتأيين الأصل والفرع له في الاشتقاق نفسه. ومن ناحية المنهج، يعد هذا البحث بحثا نوعيا بنوعه الدراسة المكتبية، لأن البيانات فيه نوعية بشكل نصوص أو خطابات يتم جمعها من خلال قراءة ومراجعة الكتب أو المؤلفات أو نتائج البحث العلمي في المجلات العلمية المحكمة أو البحوث من المؤتمرات الوطنية أو الدولية أو المتعلقة به. ثم يتم تحليل البيانات التي تم جمعها وتحليلها بشكل تفاعلي بحيث يمكن بعد ذلك استنتاج النتائج بناءً على المشكلات المبحوثة. ونتائج هذا البحث أن الاشتقاق هو أحد طرق تكوين المفردات العربية وتنميتها، والذي ينقسم إلى أربعة أنواع ، وهي: 1) الاشتقاق الصغير أو الأصغر أو الصرفي، 2) الاشتقاق الكبير، 3) الاشتقاق الأكبر (التقليب أو القلب)، 4) الاشتقاق الكُبار (النحت). وهناك مدرستان رئيسيتان في تعيين ما هو الأصل والفرع له في الاشتقاق، وهما مدرسة البصرة ومدرسة الكوفة، هما تختلفان في رأيهما في تحديد أيهما (الأصل) الرئيسي والفرع (الفروع) في الاستقاق. يعتقد علماء البصرة أن (اسم) المصدر هو الأصل والفعل فرع له، بينما يعتقد علماء الكوفة أن الفعل هو الأصل و (اسم) المصدر فرع له.الكلمات المفتاحية: الاشتقاق; فقه اللغة العربية; مدرسة البصرة ومدرسة الكوفةABSTRACTThe Arabic language is famous for its common vocabulary. Derivation is one of the ways of forming Arabic vocabulary. It is still among the ancient Arab linguists or speakers arguing about its classification and what the origin of the derivation, whether it is the source or the verb. This research aims to find out the reality of the derivation in the field of Arabic philology, whether its concept, classification, and the ionization of the origin and branch of it is in the derivation itself. From the end of the method, this research is a qualitative research of the type of desk study, because the data in it is qualitative in the form of texts or letters that are collected through reading and reviewing books, literature, or the results of scientific research in refereed scientific journals or research from national or international conferences or related to it. The collected data is then analyzed and analyzed interactively so that the results can then be deduced based on the problems investigated. The results of this research are that derivation is one of the ways of forming and developing Arabic vocabulary, which is divided into four types, namely: 1) small, smaller, or morphological derivation, 2) major derivation, 3) greater derivation (al-taqlab or al-qalb), 4) adult derivation (sculpture). There are two main schools in defining what is the origin and the branch for it in derivation, and they are the school of Basra and the school of Kufa, they differ in their opinion in determining which is the main (origin) and the branch (franchise) in derivation. Basra scholars believe that the infinitive (noun) is the origin and the verb is a branch of it, while Kufa scholars believe that the verb is the origin and the infinitive is a branch of it.